Ubiquitin-Specific Proteases UBP12 and UBP13 Act in Circadian Clock and Photoperiodic Flowering Regulation in Arabidopsis(1)([W])([OA]) - Cui, Xia (American Society of Plant Biologists, 2013)
Protein ubiquitination is involved in most cellular processes. In Arabidopsis (Arabidopsis thaliana), ubiquitin-mediated protein degradation regulates the stability of key components of the circadian clock feedback loops and the photoperiodic flowering pathway. Here, we identified two ubiquitin-specific proteases, UBP12 and UBP13, involved in circadian clock and photoperiodic flowering regulation. Double mutants of ubp12 and ubp13 display pleiotropic phenotypes, including early flowering and short periodicity of circadian rhythms. In ubp12 ubp13 double mutants, CONSTANS (CO) transcript rises earlier than that of wild-type plants during the day, which leads to increased expression of FLOWERING LOCUS T. This, and analysis of ubp12 co mutants, indicates that UBP12 and UBP13 regulate photoperiodic flowering through a CO-dependent pathway. In addition, UBP12 and UBP13 regulate the circadian rhythm of clock genes, including LATE ELONGATED HYPOCOTYL, CIRCADIAN CLOCK ASSOCIATED1, and TIMING OF CAB EXPRESSION1. Furthermore, UBP12 and UBP13 are circadian controlled. Therefore, our work reveals a role for two deubiquitinases, UBP12 and UBP13, in the control of the circadian clock and photoperiodic flowering, which extends our understanding of ubiquitin in daylength measurement in higher plants.